CompuCell3D model of cell migration reproduces chemotaxis - Dal Castel, Pedro Cenci (2023)
The introduction and conclusion of the following dissertation serve to support and summarize our research entitled ”CompuCell3D Model of Cell Migration Reproduces Chemotaxis.” In this study, we created a CompuCell3D simulation of single cell chemotaxis, a biological phenomena in which cells move in response to environmental chemical cues. We also developed an analysis scheme to analyze recordings of center of mass and polarization over time to characterize cell dynamics and kinetics. Aiming at individuals with intermediate modeling experience who lack specific understanding in the field, we offer the relevant biology, mathematics, and computational foundation in order to adequately prepare the reader. In the first topic, we discuss the biological cell and its capacity to migrate, discussing both the significance of this capacity for survival and the underlying biochemical mechanism. Second, we explore a few computational and mathematical models of cell migration, focusing on a brand-new analytical model called the Anisotropic OrnsteinUhlenbeck Process, which treats polarization in its stochastic differential equations. Finally, we go over CompuCell3D’s functionality in detail and provide a real-world example for readers to try out (needs access to a computer with Windows installed). Our research on single cell movement aims to completely characterize chemotaxis and offer tools that may be used to analyze experimental data, provided that cell polarization is measured. We discuss the significance of cell polarization measurements and the proper way to handle the issue of cell velocity when short time scales exhibit cell diffusive behavior. We suggest a procedure for measuring chemotactic efficiency as well as a way to discriminate between cell reorientation and cell drift speed modulation as chemotactic response modalities. Our simulation serves as the basis for upcoming collective migration models and may be utilized to investigate the role of particular types of white blood cells during innate immune response.